جليل الكلام و دقيقه لدى الشيعة الإمامية قبل بداية فترة الغيبة الكبرى - Edris, Mosaab Elkhair (DINIKA : Academic Journal of Islamic Studies, 2017)
This study would serve as sequel to the views of the Imami theologian Hisham bin al-Ahkam on Jalil al-Kalam and Daqiq al-Kalam by explaining the theological views of Zurarah bin A'yun, Abu Ja'far al-Ahwal, al-Fadl ibn Shazan and Banu Nubakht; it will focus on their known writings, explicating their available theological views as far as possible, on the basis of Sunni and Shi'ite sources in the context of the history of theology. The objective behind that is to explain the theological trends that emerged in the history of the Twelver Imamite community, their connections; this would, first of all, provide knowledge of the intellectual foundations of the Twelver theology, which reached its pinnacle at the hands of the theologians of the fifth century AH beginning with Shaykh al-Mufid bin Muhammad bin al-Nu'man al-Akbari al-Baghdadi. Secondly, this study would provide an understanding of the relational basis between the Twelver and the Mutazilite theological thought. I think that it is the result of a mutual cross-fertilization on the one hand, while on the other since they both derive from the same sources, they lead to similar results. It is not a case of Shi'ite subservience to a predominant Mutazilite influence because the Twelver Shi'ite theologian was conscious of his requirements in support of his doctrine, which revolves around the issue of the Imamah in Jalil al-Kalam and Daqiq al-Kalam alike. In addition, this study will also identify the real origins of the idea of limiting the imamate to twelve imams, ending with the consideration of the early Imamite scholars through which they established their arguments against their opponents in their writings and debates. This is all the more important since the titles of the Shi'ite Imami writings and from what is quoted in their debates on the issue of Imamate, do not point to the imamate of only twelve imams, as the history of the Imami Thought depicts and which starts with the period of the Minor Occultation, which lasted about 70 years from 260 to 329 AH.